(untitled) (Journal of Dhaka Medical College, 2015)
Objective: To find out the effects of ginger (Zingiber officinale) juice blood glucose in alloxan induced-diabetes mellitus in rats. Methods: This experimental study was done in the Department of Pharmacology & Therapeutics, Dhaka Medical College, Dhaka, in collaboration with the Departments of Pathology, Ibrahim Medical College, Dhaka between January and December 2009. This experimental animal study was divided into two parts, which were Experiment-1 and Experiment-2. Experiment 1 comprises of 12 rats and divided into 2 groups each group having 6 rats. Rats of group-A was non-diabetic normal control group and group-B was fed with ginger (Zingiber officinale) in a dose of 4ml/kg body weight orally through Ryles tube. Experiment-2 comprised of 12 rats divided into 2 groups each containing 6 rats labeled as group C, group D. Rats of groups C administered alloxan 150 mg/kg intraperitoneally on the 2nd day of the study. Rats of group D were administered alloxan 150mg /kg intraperitoneally and ginger (4ml/kg of body weight orally) on the 2nd day of the study. Results: The fasting blood glucose level at day 12 in the rats treated with ginger (Zingiber officinale) 4 ml /kg body weight orally daily for 12 days showed reduction in fasting blood glucose level as compared to control group, but not significant, which indicates that ginger has no effect in lowering blood glucose of normal rats. The fasting blood glucose levels at day 12 in the rats of group D (treated with ginger and alloxan) showed highly significant reduction in fasting blood glucose level as compared to diabetic control group (p<0.002). Conclusion: Consumption of ginger produced a significant antihyperglycemic effect in experimentally induced diabetic rats. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22687 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 14-17